Development and psychometric analysis of a Pediatric Oncology Nurses' Educational Needs Scale. Issue 5 (7th March 2023) - Kudubeş, Aslı Akdeniz; Semerci, Remziye; Özbay, Sevil Çınar; Ay, Ayşe; Boztepe, Handan
Abstract: Background/objectives: It is important to determine the educational needs of pediatric oncology nurses in order to maximize and implement nursing care interventions. Therefore, this study aims to develop a valid and reliable measurement tool to determine pediatric oncology nurses' educational needs and examine its psychometric properties. Design/methods: This methodological study was conducted with 215 pediatric oncology nurses in Turkey between December 2021 and July 2022. Data were collected with the "Nurse Information Form" and "Pediatric Oncology Nurses' Educational Needs Scale." IBM SPSS 21.0 and IBM AMOS 25.0 software programs were used for data analysis, and descriptive statistics were used to analyze numeric variables. Exploration and confirmatory factor analyses were performed to determine the scale's factorial structure. Results: The factorial analysis was used to test the structural validity of the scale. A five‐factor structure consisting of 42 items was developed. The Cronbach's alpha coefficient for "Illness" was .978, "Chemotherapy and Side Effect" was .978, "Another Therapy and Side Effect" was .974, "Palliative Care" was .967, "Supportive Care" was .985, and the total score was .990. Fit indices resulting from the study were χ 2 /SD: 3.961, root mean square error of approximation (RMSEA): 0.072, goodness‐of‐fit index (GFI): 0.95, comparative‐of‐fit index (CFI): 0.96, and normed fit index (NFI): 0.95. Conclusion: The Pediatric Oncology Nurses' Educational Needs Scale is a valid and reliable scale for pediatric oncology nurses to determine their educational needs.